Multiple Driver Impacts on Rocky Intertidal Systems: The Need for an Integrated Approach - Kunze, Charlotte; Wölfelschneider, Mirco; Rölfer, Lena (Frontiers in Marine Science, 2021)
Most intertidal rocky systems are exposed to severe tidal, diurnal, and seasonal changes in environmental parameters. In addition, they show extreme vulnerability to anthropogenic impacts. Research on multiple drivers is therefore crucial to understand the complexity of their potential interactions. Here, we first give an overview of the natural environment and impacts of climate change on rocky shore intertidal systems, and then focus on the impacts of multiple drivers. We further provide a summary of existing multiple driver studies in the literature with the aim for a better understanding of multiple driver interactions. As multiple drivers can affect rocky shore intertidal systems at different spatial and temporal scales, and the outcome of their effects are still more of an “ecological surprise,” we recommend a more widespread assessment of the environmental and biological context. We propose a new, integrated approach based on existing literature: this complements previous frameworks but with an improved understanding of co-occurring multiple driver systems of the rocky intertidal, in order to find management solutions based on accurate and informed predictions in these times of global change.